2016
DOI: 10.1136/bmjopen-2015-010790
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing women's attitudes towards antenatal vaccines, group BStreptococcusand clinical trial participation in pregnancy: an online survey

Abstract: ObjectivesTo explore factors influencing the likelihood of antenatal vaccine acceptance of both routine UK antenatal vaccines (influenza and pertussis) and a hypothetical group B Streptococcus (GBS) vaccine in order to improve understanding of how to optimise antenatal immunisation acceptance, both in routine use and clinical trials.SettingAn online survey distributed to women of childbearing age in the UK.Participants1013 women aged 18–44 years in England, Scotland and Wales.MethodsData from an online survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 11 publications
8
34
2
Order By: Relevance
“…Contrary to the usual emphasis on minimizing the number of visits to cause as little inconvenience as possible in many standard vaccine studies, it seems that offering additional time, scans and appointments could improve the likelihood of pregnant women participating, whereas incentives such as vouchers or money would have little effect on recruitment. A previous study of mostly non‐pregnant women had indicated that those with children might be more likely to take part in a clinical vaccine trial , although the differences here were not significant. In the same study among non‐pregnant women, 32% of respondents indicated they would be very/fairly likely to take part compared with 23.8% of the pregnant women surveyed here.…”
Section: Discussioncontrasting
confidence: 75%
“…Contrary to the usual emphasis on minimizing the number of visits to cause as little inconvenience as possible in many standard vaccine studies, it seems that offering additional time, scans and appointments could improve the likelihood of pregnant women participating, whereas incentives such as vouchers or money would have little effect on recruitment. A previous study of mostly non‐pregnant women had indicated that those with children might be more likely to take part in a clinical vaccine trial , although the differences here were not significant. In the same study among non‐pregnant women, 32% of respondents indicated they would be very/fairly likely to take part compared with 23.8% of the pregnant women surveyed here.…”
Section: Discussioncontrasting
confidence: 75%
“…Korean women of childbearing age appeared not to be adequately informed by healthcare providers (HCPs) about the vaccinations recommended in pregnancy 54. In a recent UK survey involving 1013 women of childbearing age, multiparous women were more likely to accept antenatal vaccinations including pertussis and to participate in vaccine trials during pregnancy compared with primiparous 55. In addition, HCPs in the UK were the most important and valuable source of information for pregnant women 55.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent UK survey involving 1013 women of childbearing age, multiparous women were more likely to accept antenatal vaccinations including pertussis and to participate in vaccine trials during pregnancy compared with primiparous 55. In addition, HCPs in the UK were the most important and valuable source of information for pregnant women 55. Similarly, in Australia, new mothers were more likely to be vaccinated if they had heard of the disease and the benefits of vaccination from an HCP 56.…”
Section: Resultsmentioning
confidence: 99%
“…This qualitative study was conducted as part of a larger project with the overall aim of obtaining more in-depth information on the attitudes and opinions of pregnant women and healthcare professionals towards antenatal vaccination, GBS, a potential GBS vaccine and participation in clinical trials during pregnancy, which were prominent issues raised during an initial large-scale survey of British women of child-bearing age (24,25).…”
Section: Introductionmentioning
confidence: 99%